2016
DOI: 10.1111/apm.12609
|View full text |Cite
|
Sign up to set email alerts
|

The human gastrointestinal tract and oral microbiota in inflammatory bowel disease: a state of the science review

Abstract: Inflammatory bowel disease (IBD) includes a spectrum of diseases from ulcerative colitis (UC) to Crohn's disease (CD). Many studies have addressed the changes in the microbiota of individuals affected by UC and CD. A decrease in biodiversity and depletion of the phyla Bacteroidetes and Firmicutes has been reported, among others. Changes in microbial composition also result in changes in the metabolites generated in the gut from microbial activity that may involve the amount of butyrate and other metabolites su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 82 publications
2
55
0
Order By: Relevance
“…Ulcerative colitis is a well‐described clinical disease with an ill‐defined aetiology and remains very challenging to treat. Once triggered in genetically susceptible individuals, an impaired immune response develops, leading to a lack of tolerance to the resident gut microbiota (Lucas Lopez, Grande Burgos, Galvez, & Perez Pulido, ; Thompson‐Chagoyan, Maldonado, & Gil, ; Zhang et al., ). The gut bacteriome is not yet clearly defined, and neither is the mycobiome or virome (Clavel, Lagkouvardos, & Hiergeist, ; Gupta et al., ; Nash et al., ; Virgin, ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis is a well‐described clinical disease with an ill‐defined aetiology and remains very challenging to treat. Once triggered in genetically susceptible individuals, an impaired immune response develops, leading to a lack of tolerance to the resident gut microbiota (Lucas Lopez, Grande Burgos, Galvez, & Perez Pulido, ; Thompson‐Chagoyan, Maldonado, & Gil, ; Zhang et al., ). The gut bacteriome is not yet clearly defined, and neither is the mycobiome or virome (Clavel, Lagkouvardos, & Hiergeist, ; Gupta et al., ; Nash et al., ; Virgin, ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that the composition of the intestinal bacterial microbiota can correlate with the development of, or resistance to, obesity (25), malnutrition (26, 27), and allergic disease (28) and may also influence cognitive function and development (29). The intestinal microbiota is not limited to prokaryotes (30), with archaea and eukaryotes potentially contributing to clinical variation (31, 32). …”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Bacterial microflora can also participate in the pathogenesis of ulcerative colitis in humans [45][46][47]. Interestingly, a large number of previous studies indicated that H. perforatum extracts, especially alcoholic ones had remarkable anti-bacterial properties [48].…”
Section: Gross Appearance Of the Colonic Mucosa In Experimental Groupsmentioning
confidence: 99%